Flow aeration and surface fluctuations in moderate-slope stepped chute: from aeration inception to fully developed aerated flow. Issue 6 (2nd November 2022) - Wang, Hang; Bai, Zhongtian; Liu, Xuechun; Bai, Ruidi; Liu, Shanjun
Abstract : Although stepped chute flows have been studied for a variety of chute geometries and flow conditions, reports on air–water flow development in the fully developed aerated region are not as comprehensive as those in the nonaerated and developing aerated regions. In this paper, skimming air–water flows in a large stepped chute (1V:2.5H) were studied comparatively for two step heights, showing different stages for velocity and aeration development downstream the inception point. The mean air concentration reached a constant level while the bubble frequency kept increasing slowly in the fully developed region. The developed mean air concentration was related to the sloping angle, step height and flow discharge. The results provided possible prediction of maximum bubble frequency and its longitudinal evolution, and a glance at the scale effect on it. The free-surface fluctuations and splash height were presented, with particular attention to the effects of step height on the turbulence and aeration modification.